2022
DOI: 10.1155/2022/9978282
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Body Size Change on Off-Center Cervical Point and Face Doses in Patients Undergoing Nasopharyngeal Carcinoma Radiotherapy

Abstract: Nasopharyngeal carcinoma (NPC) is a clinically multiple malignant tumor. At present, with the increase in the infection rate of Epstein-Barr virus, the incidence of nasopharyngeal carcinoma is also increasing day by day. To explore the effect of body size change on off-center cervical point and face doses in patients with nasopharyngeal carcinoma (NPC) undergoing radiotherapy, in total, 100 patients with NPC from January 2019 to May 2020 in our hospital were selected for retrospective analysis, and they all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%